(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the early outcomes of transabdominal preperitoneal (TAPP) laparoscopic repair for bilateral inguinal hernia. Methods: A combined retrospective and prospective descriptive study was conducted on 36 patients diagnosed with bilateral inguinal hernia who underwent TAPP repair at Hai Phong University of Medicine and Pharmacy Hospital and Viet Tiep Friendship Hospital from January 2019 to March 2026. Clinical characteristics, intraoperative and postoperative outcomes were recorded and analyzed. Results: The mean age was 63.5 ± 11.1 years. The mean operative time was 113.9 ± 18.5 minutes. Intraoperative complications were low, with spermatic vessel bleeding being the most common (8.3%). The mean time to first flatus was 18.0 ± 2.9 hours. The mean postoperative pain score (VAS) on day 1 was 5.1 ± 0.8. The mean hospital stay was 6.0 ± 1.4 days. Early postoperative outcomes were favorable, with 100% of patients achieving good or fair results. Conclusion: TAPP repair for bilateral inguinal hernia is a safe and effective technique, associated with rapid recovery and low complication rates.